Philosophy at school: deafness on focus - Brennan Cavalcanti Maciel Modesto; Vera Lúcia Maria Cavalcanti Maciel Modesto (Universidade Estadual de Alagoas, 2021)
It is a hard task to think about teaching Philosophy on the XXI century. After all, Philosophy itself performs features that were not seen during its genesis or golden periods. For this purpose, it is necessary to make a double nature investigation. On one side, there are logical and grammatical analysis of the conceptual conceptions about School, Teaching and Deafness; on the other, there is a genetic analysis of the hands-on modus operandi at School. Taking as reference Simón Rodríguez's perspective about Popular School, the enquiry approaches its institutionalization, that is, the necessity of responding to social demands -not rarely, represented by the subjection to superior instances of diverse natures, understood as curricular component. Brief considerations were made about the Philosophy teaching process itself and its boundaries within the Basic School context, so there could be a way of debouching in a discussion about the processes of inclusion of deaf people in these procedures. It is also known that the deaf community, in particular, carries an eminent obstacle, conventionally named as "language barrier". From the abovementioned discussions, it is possible to synthesize the specific difficulties encountered in the relation between Philosophy as a curricular component and its teaching to deaf people, particularly the topic of untranslatable philosophical concepts, raising the idea that the effectiveness of teaching Philosophy to deaf is beyond the pure and simple bilingualism.